Does corporate sustainability disclosure mitigate earnings management: empirical evidence from Jordan - Ahmad Yuosef Alodat (17900027) (2023)
This paper aims to investigate the relationship between sustainability disclosure practices and earnings management in the Jordanian context. Based on an analysis of 66 non-financial firms listed on ASE, spanning the period of 2017–2020. The findings revealed that companies' compliance with the disclosure of sustainability improves their ethical behavior, which limits earnings management practices and increases the reliability of their financial statements. The findings have implications for regulators, corporate executives, practitioners, policymakers, top management, and business partners. More corporate sustainability practices present more trustworthy information and more sustainable performance of the economic. To the best of the authors’ knowledge, this is the first study to examine the relationship between the extent of sustainability disclosure and earnings management in Jordanian firms. Moreover, two models were used for earnings management, which adds value to the existing literature. Other Information Published in: International Journal of Disclosure and Governance License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1057/s41310-023-00213-4